'Things should be better' – Immobility, labour and the negotiation of hope amongst young Ghanaian craftsmen. (October 2021) - Clifford Collard, Niamh Jane
Drawing on an ethnography of life in a Ghanaian weaving workshop, this article traces the intersections between young rural weavers' affective labour, hope and their experiences of immobility. Hope is explored as an ambivalent resource which shapes the shared, social materiality of their craftwork, the spiritual beliefs which give meaningful shape to the challenges of craft livelihoods and the imaginaries and lived experiences which compose young weavers' sense of migration and mobility. Entangled in the precarious logics of late capitalism, these hopes simultaneously offer young craftsmen a sense of existential mobility, whilst curtailing and circumscribing possibilities for sustained and systemic change. In this, the 'not-yet' hopefulness of immobility is examined as a complex affective and political field, shot through with tense anticipation, longing and disappointment.